Natural drugs targeting inflammation pathways can be used to treat atherosclerosis - Song, Xiayinan; Wang, Xiaoming; Wang, Danyang; Zheng, Zhenzhen; Li, Jie; Li, Yunlun (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) is the chronic gradual degradation of arteries in combination with inflammation. Currently, the main research focus has been on interactions between inflammatory cells, inflammatory mediators, and immune mechanisms, while some studies have reported natural drugs were exerting a critical role against AS, whereas the usage of the natural drugs were always limited by various factors such as poor penetration across biological barriers, low bioavailability and unclear mechanisms. Herein, we reviewed the potential targets for inflammation against AS, discussed the underlying mechanisms of natural drugs for AS, particularly highlighted the dilemma of current research, and finally offer perspectives in this field.